The public sector in India : a survey - Dagli, Vadilal (Bombay : Vora, 1969)
This book deals with the public sector in India which have emerged as an important level of Indian economy growth.
Includes bibliographical references: p. [290]-296.
oo 12/11/2018
Loans
Keywords: Government business enterprises